Throwing performance is associated with muscular power - Bourdin, M.; Rambaud, O.; Dorel, S.; Lacour, J.-R.; Moyen, B.; Rahmani, A. (International Journal of Sports Medicine, 2010)
The aim of the present study was to test the hypothesis that performance in throwing events is associated with muscular characteristics of both upper and lower limbs. Thirty-eight male throwers volunteered to participate. Bench press and half squat tests were conducted on a guided barbell. The barbell displacement signal was recorded using a kinematic system. Maximal power, corresponding optimal velocity and force (PmaxS, VoptS, FoptS and PmaxBP, VoptBP, FoptBP for half squat and bench press, respectively) were extrapolated from the power-velocity relationship. Lower limb stiffness (K) was determined during maximal hopping. The results demonstrated that PmaxS and PmaxBP were correlated with each thrower's season's best performance (SBP, r=0.54, p<0.01 and r=0.71, p<0.001, respectively). PmaxS expressed relative to body mass was not correlated with SBP. K was significantly correlated with SBP (r=0.66, p<0.001). The relationship between PmaxBP expressed relative to body mass and SBP remained significant (r=0.54, p<0.001). The results of the study suggest that high strength and stiffness values for lower limbs and strength and velocity characteristics for upper limbs may be associated with athletic throwing performance.